The urethro-prostatic angle as a practical sonographic index for estimating prostatic size in dogs - Groppetti, Debora; Pecile, Alessandro; Giussani, Elisa; Bronzo, Valerio; Raneri, Federica; Faverzani, Stefano (Frontiers in Veterinary Science, 2026)
IntroductionProstatomegaly is a common condition in adult, intact dogs. Abdominal ultrasonography is currently considered the method of choice for assessing the prostate size using volume-based formulas. However, objectively defining an enlarged prostate remains challenging, even for experienced operators. This is mainly due to the wide variability in dog sizes and the partially intrapelvic position of the gland, which can limit its complete visualization. This study aimed to explore the reliability of a new, practical, and less operator-dependent parameter, the urethro-prostatic angle (UPa), for estimating canine prostate volume via B-mode ultrasonography.Materials and methodsSixty-three dogs were enrolled, and prostatic volume was assessed using the equation proposed by Ruel et al., which is based on measurements of the gland's length, height, and width obtained from sagittal and transverse scans. Furthermore, to distinguish between normal and enlarged prostates, a second Ruel formula, which includes age and body weight, was also applied.ResultsThe urethro-prostatic angle was successfully measured in all dogs and correlated significantly with prostate volume (p < 0.001). A UPa cutoff value of 96.52° effectively discriminated between normal (UPa ≤ 96.52°) and enlarged (UPa > 96.52°) prostates, achieving a sensitivity of 100% and a specificity of 71.7%. Furthermore, inter-operator variability was not significant (p = 0.2).ConclusionIn contrast to traditional volume estimation methods, the measurement of the UPa is independent of canine body size, prostatic gland position, and operator skill. These findings suggest that the UPa is a promising, repeatable, and practical parameter for the reliable estimation of prostatomegaly in dogs.